Characterization of the structural, physicochemical, and functional properties of soluble dietary fibers obtained from the peanut shell using different extraction methods - Wang, Lei; Fan, Rui; Yan, Yanhua; Yang, Shuo; Wang, Xuesong; Zheng, Baiqin (Frontiers in Nutrition, 2023)
Objective To propose a possible solution for a peanut by-product, peanut shell (PS), this study evaluated the effects of different methods, including enzymatic extraction (E-SDF), microwave extraction (M-SDF), and pulsed electric field extraction (PEF-SDF), on the characterization of soluble dietary fibers (SDFs) from PS. Methods We determined the physicochemical properties, including water- and oil-holding capacities (WHC and OHC), emulsifying properties, rheological properties, functional properties, including pancreatic lipase activity inhibition (PRAI), glucose and cholesterol adsorption capacities (GAC and CAC), and the structural properties of SDFs. Results The results showed that PEF-SDF possessed the highest WHC, OHC, and emulsifying properties. M-SDF and PEF-SDF appeared to have more complex and porous structures, and they showed small molecular weights. Notably, PEF-SDF showed the strongest capacities in CAC, GAC, and PRAI. Conclusions The results indicate that PEF-SDF is a potential SDF preparation method for a promising dietary fiber (DF) source, PS.